Entre política econômica e política Criminal: a aplicabilidade do acordo de Leniência no sistema brasileiro de defesa da Concorrência. - Leite, Filipe Mendes Cavalcanti (2015)
This paper aims to shed some light on the applicability of leniency agreement in the Brazilian System of Competition Defense. For this, it’s necessary a rescue on the development of the idea of freedom, and then get to free competition as principle underlying the Economic Order. The democratic state, established in the 1988 Constitution, is the contemporary stage of defense of legal, economic and social values which are intended to guarantee national development, and promote the construction of a free, fair and inclusive society. It will be seen that the mentioned Economic Policy correlates with the Criminal Policy idealized by the State. There will be a theoretical and historical establishment that takes account of the evolution of the discipline of Antitrust in Brazil. There will also find space in this paper for the illustration of the idea of Antitrust Sanctioning Law to see how the Government may, very effectively, investigate and punish officials based on their own standards, serving as a counterpoint to the Economic Criminal Law. This route of parallel paths between administrative and legal marks of Antitrust is clearly reflected in the Leniency Agreement institute. Thus, a conceptual frame about what will be the object spanned by the leniency agreement will be presented: cartels. Will fetch up the demonstration of various types of cartel, with special emphasis on bidding cartels. Finally, the work dissects the institute's Leniency Agreement itself, solidifying its legislative and conceptual basis, and presenting their rules. Through the combination of legal rules, will be shown the way to be observed when entering into an agreement. Based on this view, will be presented the Historical of Conducts of a Leniency Agreement in a bidding cartel. Also adds up the context of the Leniency Agreement in international models implemented in the United States and European Union. In addition, this paper will seek to give lights to the criteria for distinguishing between administrative predictions arising from decisions made by administrative courts, especially the Administrative Council for Economic Defense, and its possible implementation in criminal area, suggesting alternatives that may match in an harmonic way the application of the institute and the preservation of its effects.